1994
DOI: 10.1073/pnas.91.3.974
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic photoreceptor cell death in mouse models of retinitis pigmentosa.

Abstract: Retinitis pnentsa (RP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
321
1
8

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(342 citation statements)
references
References 19 publications
12
321
1
8
Order By: Relevance
“…Thus, it would be of value to analyse the presence of IAP proteins and analogs in RPE cells during serum deprivation. Previous studies have suggested that endogenous FGFs act as protection factors in vivo by showing a dramatic upregulation of FGF gene expression in response to cell death in various retinal degeneration models (Portera-Gailleau et al, 1994;Gao and Holly®eld, 1996). We have con®rmed that this is the case in retina, by demonstrating that inhibition of the binding of endogenous FGFs to their receptors accelerates and increases retinal cell apoptosis (Guillonneau et al, 1998a).…”
Section: Discussionmentioning
confidence: 53%
“…Thus, it would be of value to analyse the presence of IAP proteins and analogs in RPE cells during serum deprivation. Previous studies have suggested that endogenous FGFs act as protection factors in vivo by showing a dramatic upregulation of FGF gene expression in response to cell death in various retinal degeneration models (Portera-Gailleau et al, 1994;Gao and Holly®eld, 1996). We have con®rmed that this is the case in retina, by demonstrating that inhibition of the binding of endogenous FGFs to their receptors accelerates and increases retinal cell apoptosis (Guillonneau et al, 1998a).…”
Section: Discussionmentioning
confidence: 53%
“…Unlike the rod photoreceptors of the Rds/Rds mouse~Sanyal & Jansen, 1981!, all three strains of the rd-3 homozygotes clearly are able to assemble OS discs, although they are not all normal in either size or orientation. In considering the overall pattern of cell loss, the rd-3/rd-3 degeneration shows no apparent preference for rods over cones or for center versus periphery and thus differs from the rd/rd mouse where rods are lost The TUNEL data show that photoreceptors die by apoptosis in this mutation as in every other retinal degeneration described to date, whether inherited~Chang et al, 1993b; Portera-Cailliau et al, 1994;Tso et al, 1994;Smith et al, 1995;Ikeda et al, 1999;Guarneri et al, 2004!, or induced~Shahinfar et al, 1991Cook et al, 1995!. In the murine retinal degenerations described above, the developmental stage at which the effect of the mutant genes becomes expressed varies widely. The earlier the onset, as in rd, the less mature the OS will be as photoreceptor cells begin to die en masse.…”
Section: Discussionmentioning
confidence: 93%
“…18,19 At the same time, calpains directly proteolyse executioner caspases, mediating their activation, 20,21 as well as proapoptotic Bcl-2 family members that eventually cause the release of apoptogenic factors from the mitochondria involved in the triggering of the caspase cascade. [22][23][24] While the time course of developmental apoptosis in the mouse retina has been extensively described in several studies, 10,[25][26][27] the biochemical death pathways involved are not fully understood. In particular, relatively little is known about the molecular mechanisms of developmental apoptosis in cone photoreceptors, due to the paucity of cone-specific markers at early stages of development.…”
Section: Introductionmentioning
confidence: 99%